THE SYSTEM OF TECHNICAL AND ECONOMIC CRITERIA AS THE BASE OF CRITERIAL FEASIBILITY OF AUTOMATED SYNTETHSIS OF MECHANICALASSEMBLYROBOTIC TECHNOLOGIES - Kyrylovych, V. (Енергетика і автоматика, 2016)
The system of criteria for choice the optimal robotized mechanical assembly technology was proposed as the result of analytical generalizations. Along with the othersthere are detailed content, essence and analytical formulas are submitted for the proposed technical and economic criteria any of which can be used as a global optimality criterion when choosing a robotic assembly technology of their ultimate set that synthesized at the famous technical basis of flexible manufacturing cell.